Lessons from India's implementation of Doha Declaration on TRIPS and Public Health - Nanditta Batra (South Centre, 2022)
The major bone of contention between the developed and developing countries in the TRIPS negotiations was patents for pharmaceuticals. The US-led developed countries bloc argued in favour of patents for pharmaceuticals amidst opposition from Brazil, India and other countries. Ample evidence, including patented AZT for HIV/AIDS treatment, showed that patents could make life saving drugs prohibitively expensive. Notwithstanding the effect of patents on access to medicines, Article 27 of the TRIPS Agreement ordained patents for inventions "in all fields of technology". While the genie was out of the bottle in the form of patents for pharmaceuticals, the developing countries were able to extract some procedural and substantive flexibilities like transition period, parallel importation and compulsory licensing to leverage the IP system to further public health. However, there was uncertainty with respect to the interpretation of TRIPS agreement, scope of the flexibilities and Member States' rights to use them. It is in this background that the historic Doha Declaration on the TRIPS Agreement and Public Health assumed importance as it reaffirmed the rights of the Member States to take measures to protect public health, reconciled the interpretative tensions in the text of TRIPS Agreement and clarified the scope of some of the flexibilities and attempts to find solutions to the problems faced by countries that do not have sufficient manufacturing facilities. The Declaration which was initially dismissed by some scholars as "non-binding," "soft law" has been held by WTO Dispute Settlement Body (DSB) to constitute a "subsequent agreement" which must be followed in interpreting the provisions of TRIPS Agreement (Australia-Tobacco Plain Packaging Case)
Keywords: 300; Access to Medicines; Compulsory Licenses; Dispute Settlement; Doha Declaration on the TRIPS Agreement and Public Health; Flexibilities; Health; India; Intellectual Property; Intellectual Property Rights (IPRs); Parallel Importation; Patent; Patentability Criteria; Pharmaceuticals; Public Health; Transition Period; TRIPS; TRIPS Agreement; TRIPS Flexibilities; World Trade Organization (WTO)